Stoichiometric synthesis of tetragonal phase pure lead titanate under mild chemical conditions employing NaOH and KOH - Apinpus Rujiwatra (2018)
Submicron- to nanometer-sized particles of single phase lead titanate have been prepared in stoichiometric proportion under mild hydrothermal conditions employing either potassium or sodium hydroxides as alkali mineralizers. In conjunction with reaction temperature and time, these variables played a crucial role in determining the habit of crystalline particles. The feasibility of using sodium hydroxide as an alternative for potassium hydroxide in the preparation of nanopowders of lead titanate was demonstrated. The influence of the preparative conditions, e.g. reaction temperature and time, on phase formation, morphology, the habit of crystalline particles, size and size distribution, was investigated. © 2005 Elsevier B.V. All rights reserved.